2009
DOI: 10.1007/s12311-009-0118-4
|View full text |Cite
|
Sign up to set email alerts
|

PTPRR, Cerebellum, and Motor Coordination

Abstract: Tyrosine phosphorylation is a powerful mechanism of modulation for proliferation, differentiation, and functioning of neurons. The protein products of the neuronal mouse gene PTPRR are physiological regulators of mitogen-activated protein kinase (MAPK) activities. PTPRR −/− mice display deficits of motor coordination and balance skills. PTPRR gene orthologues are found in many vertebrates. Recent observations suggest that the human episodic ataxia 2 (EA2) and spinocerebellar ataxia types 6 (SCA6), 12 (SCA12), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This transdifferentiation has been shown to be driven by protein tyrosine phosphatases, which play a key role in neuronal development [ 25 ], including PTPRA [ 26 ] and PTPB1 [ 27 ]. Here, we found PTPRB (KSC p -value 0.937) and PTPRR (KSC p -value 0.939)—both are involved in neuronal differentiation [ 28 , 29 ] and thus may play a role in neuroendocrine differentiation. In addition, it is known that E-cadherin is downregulated by AR [ 30 ], and here we find its binding partner, CDH3 [ 31 ], may also be repressed directly by AR (KSC p -value = 0.957).…”
Section: Resultsmentioning
confidence: 93%
“…This transdifferentiation has been shown to be driven by protein tyrosine phosphatases, which play a key role in neuronal development [ 25 ], including PTPRA [ 26 ] and PTPB1 [ 27 ]. Here, we found PTPRB (KSC p -value 0.937) and PTPRR (KSC p -value 0.939)—both are involved in neuronal differentiation [ 28 , 29 ] and thus may play a role in neuroendocrine differentiation. In addition, it is known that E-cadherin is downregulated by AR [ 30 ], and here we find its binding partner, CDH3 [ 31 ], may also be repressed directly by AR (KSC p -value = 0.957).…”
Section: Resultsmentioning
confidence: 93%
“…It was found to be overexpressed in CRPC and the high expression was related to poor prognosis. This is extremely striking because PTPRR belongs to the family of protein tyrosine phosphatases (PTPs), which regulates proliferation, differentiation, and function of cancer cells by dephosphorylating tyrosine (for example, tyrosine in mitogen-activated (Noordman et al, 2006;Schmitt et al, 2009). Several studies have shown that the expression of PTPRR is decreased in several cancers including colorectal carcinomas, cervical cancer, and oral squamous cell carcinoma due to high methylation (Laczmanska et al, 2013;Su et al, 2013;Chang et al, 2014;Woźniak et al, 2014), suggesting a tumor suppressive role for PTPRR (Menigatti et al, 2009;Su et al, 2013;Duś-Szachniewicz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current knowledge, the PTPRR gene encodes a transmembrane protein known as protein tyrosine phosphatase receptor type R. It may be of particular relevance to the motor coordination function of the central nervous system and may be involved in oncogenesis in the digestive system, as gene knockout mice display an ataxia phenotype while PTPRR are epigenetically silenced in colorectal carcinoma (Menigatti et al, 2009). Further studies have shown that PTPRR is predominately expressed in adult mice cerebellum Purkinje cells, and involved in the function of the central nervous system by regulating ERK1/2 phosphorylation (Schmitt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%